2012
DOI: 10.1590/s0103-64402012000400020
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of non-surgical treatment to reduce il-18 levels in the gingival crevicular fluid of patients with periodontal disease

Abstract: The aim of this study was to evaluate the effectiveness of the non-surgical periodontal treatment in reducing the gingival crevicular fluid (GCF) levels of IL-18 from inflamed periodontal sites. Fourteen patients with periodontal disease were included, being 9 patients with chronic periodontitis (mean age: 48.8 SD ± 7.4 years) and 5 patients with gingivitis (mean age: 43.6 SD ± 11.8). The patients were divided in the following groups: gingivitis sites from periodontitis patients (sites GP), periodontitis sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 14 publications
1
12
0
2
Order By: Relevance
“…It is reported that IL-18 levels in gingival crevicular fluid are elevated in sites of periodontal disease [48]. This is compatible with downregulation of the NLRP3 inflammasome in affected epithelia as reported in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…It is reported that IL-18 levels in gingival crevicular fluid are elevated in sites of periodontal disease [48]. This is compatible with downregulation of the NLRP3 inflammasome in affected epithelia as reported in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In periodontitis, the local inflammatory reaction to bacterial infection activates the innate immune system, resulting in the release of an array of cytokines and other mediators and propagation of inflammation through the gingival tissues (10,11). The failure to encapsulate this "inflammation front" within gingival tissue results in the expansion of the response to adjacent alveolar bone (10).…”
Section: Introductionmentioning
confidence: 99%
“…The failure to encapsulate this "inflammation front" within gingival tissue results in the expansion of the response to adjacent alveolar bone (10). Moreover, the host response is influenced by several possible risk factors including genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Учитывая, что патогенез пародонтита большинство авторов связывают с нарушением микробиоты ротовой полости и механизмов местного иммунитета, можно полагать, что успехи в развитии концепции патогенеза, диагностики и лечения заболевания могут быть связаны с иммунологическими исследованиями иммунологии полости рта и оценкой свойств ротовой жидкости (РЖ) [6,9]. Это связано с тем, что по мере прогрессирования пародонтита происходит разрушение мягких тканей, деструкция костной ткани и высвобождение биологически активных веществ, которые могут быть определены в РЖ и затем рассматриваться как кандидаты на роль биомаркеров этого заболевания.…”
Section: Abstract: Periodontitis Oral Fluid Cytokines Diagnostic Eunclassified
“…При воспалении тканей пародонта уровень факторов иммунной защиты в РЖ повышается, например, лактоферрина, секреторного иммуноглобулина А [2, 3]. Огромное число исследований посвящено изучению цитокинового статуса, играющего ключевую роль в патогенезе пародонтита, но их результаты отличаются крайней противоречивостью [7,8,9,12], что затрудняет применение полученных результатов в дальнейших изысканиях и их внедрение в клиническую практику. Это определило цель данного исследования -дать характеристику цитокинового статуса ротовой жидкости у больных хроническим пародонтитом.…”
Section: Abstract: Periodontitis Oral Fluid Cytokines Diagnostic Eunclassified